Evolutionary History of DMSP Lyase-Like Genes in Animals and Their Possible Involvement in Evolution of the Scleractinian Coral Genus, Acropora - Chiu, Yi-Ling; Shinzato, Chuya (Frontiers in Marine Science, 2022)
Dimethlysulfoniopropionate (DMSP) lyase is an enzyme that mediates cleavage of DMSP into dimethyl sulfide (DMS) and acrylate. DMS is an aerosol substance that may affect cloud formation, solar radiation and ocean temperatures. DMSP lyases in marine organisms, such as marine bacteria, release DMS, which might contribute to atmosphere-ocean feedback. Although DMSP lyases were first identified in marine bacteria, eukaryotic DMSP lyases or genes similar to DMSP lyase, DMSP lyase-like (DL-L) genes have been found not only in coccolithophores (Emiliania huxleyi) and symbiotic algae of the Family Symbiodiniaceae, but also in animals, including scleractinian corals (Cnidaria: Anthozoa: Hexacorallia). Comparative genomic analysis showed that gene expansion events of DL-L genes have occurred specifically in the scleractinian genus, Acropora. In the present study, we performed molecular identification of DL-L genes in Acropora digitifera. Thirteen full-length Open Reading Frames were isolated, confirming that these duplicated DL-L genes are likely expressed. A comprehensive survey of available transcriptomic databases revealed that DL-L genes have been identified not only in scleractinians (Hexacorallia), but also Octocorallia (Anthozoa) and even in a jellyfish (Cnidaria: Hydrozoa). Molecular phylogenetic analyses showed that although some sequences from cnidarian transcriptomic databases apparently originated with their symbiotic algae, cnidarian sequences from Anthozoa and Hydrozoa clustered together, indicating that these evolved from a gene in the last common ancestor of Cnidaria, dating to the Precambrian. Interestingly, cnidarian species possessing DL-L genes apparently occur only in coral reefs or shallow, warmer environments, suggesting that these genes may be essential for animals to survive in such environments. Acropora-specific duplicated DL-L genes, which originated during the past warm geological periods, may enable them to adapt to environmental changes.